I-129 DETERMINATION IN EVAPORATOR CONCENTRATE USING OXIDATIVE EXTRACTION AND CHROMATOGRAPHIC RESIN - Thiago César de Oliveira; Roberto Pellacani Guedes Monteiro; Geraldo Frederico Kastner; Arno Heeren de Oliveira (Brazilian Journal of Radiation Sciences)
Determination of long-lived radionuclides is very important for study of the radioactive waste final deposition. In this work will be studied 129I radionuclide which present 1.6 x 107 years half-life, β-particle-emitting (Emax = 194 keV) and X-ray-emitting (E = 29.78 keV). It’s produced primarily from fission of 235U and 239Pu and for fission induced by thermal neutrons. For this reason, radiochemical procedures for 129I determination in evaporator concentrate wastes from nuclear power plants were carried out. The first procedure was based on oxidative extraction and alkaline absorption and the second one, was based on selective extraction using a chromatographic resin in order to separate iodine from its interferents. After the separation steps, the iodine activity was measured by ultra low gamma spectrometry technique. To set up the yield recovery for 129I, a tracer solution of 129I was used in order to follow the behavior of iodine during the separation steps. The yield recovery for iodine was around 75-80% for the first procedure and 80-85% for the second. The two procedures used mutually, ensure a greater efficiency in the separation of iodine from their respective interferents.